Responsabilidad ambiental en el complejo turístico Pisagua del cantón Montalvo - Piza Castro, Nori Natividad (2018)
The norms on environmental responsibility are vital elements for a good sustainable development, that is why both the public and private companies and the population in general, seek to apply alternatives that promote the care and protection of our environment, and therefore achieve a life more healthy to through this create autonomous awareness that allows safeguarding our environment, so that our environmental habits can make the difference between deterioration and protection. In this area, this work demonstrates how the practice of environmental responsibility is managed in the Pisagua Tourist Complex, which has become a bit complex due to the lack of environmental awareness in that place. For these reasons, the following research work aims to promote good environmental practices from the perspective of sustainable development that synthesizes the importance of developing tourism framed in this area, in order to raise awareness in society and determine the extent of contamination and prevention they have with the environment.